Aplikasi Pendokumentasian Layanan Balai Desa Muara Kintap Berbasis Web - Rahmi Azizah Muksin; Khairul Anwar Hafizd; Nina Mia Aristi; Herpendi; Fathurrahmani (LPPM Universitas Nias Raya, 2023)
The administrative and service division is in charge of handling and administering services that can be provided to the community at the Muara Kintap village hall. However, the public service data recording system is still manual by recording it in a book. This requires a lot of paper and of course requires a lot of budget and there is a risk of data loss, for example in the event of a fire, the book is tucked away, lost and so on. In this study, the authors built a system entitled Web-Based Muara Kintap Village Hall Service Documentation Application. This system aims to assist employees in recording community service data in a computerized manner, storing data safely using a database so that the data search process will also be easier. This system helps the public in submitting service requests easily online. The community can access the system, see what types of services are available and can submit requests for services by filling out form data through the system without having to come to the Muara Kintap village hall. The system development model uses the waterfall model. This system was built using a web-based software development approach using a MySQL database. The designs used are Entity Relationship Diagram (ERD) and Unified Modeling Language (UML). The programming language used is Hypertext Preprocessor (PHP) and the framework used is codeigniter 3. System testing using blackbox testing shows that all system functionality can run well and as expected by 100%.